The ICC’s Appeals Chamber Judgments in the Jordan Case Regarding Al Bashir and Ntaganda Case: Victories for the Fights against Impunity and Immunity for Serious Crimes - Aghem Hanson Ekori (Polit Journal Scientific Journal of Politics, 2021)
The creation of the ICC was a turning point in the fights against impunity for serious international crimes affecting mankind. Accordingly, the ICC does not recognise any form of immunities before its jurisdiction. Consequently, individuals and senior state officials cannot rely on any form of immunities if accused of any of the crimes within the jurisdiction of the Court. In the Jordan case regarding Al Bashir’s immunity, the ICC’s Appeals Chamber held that by ratifying the Rome Statute, states parties have consented to waive the immunity of their officials regarding proceedings before the Court. As a result of this, there is no immunity between the Court and states parties and between states parties themselves, and Sudan was bound by the Statute of the Court based on the United Nations Resolution 1593. In the Ntaganda case, the Court held there is no impunity for serious international crimes before its jurisdiction. This article examines both cases and concludes that while in the Jordan case there is victory for serious international crimes and the fights against human rights violations over immunity before the ICC, there is also victory for serious international crimes over impunity before the Court as seen in the Ntaganda case.